Common and rare variants associating with serum levels of creatine kinase and lactate dehydrogenase - Ragnar P. Kristjansson (Nature Portfolio, 2016)
Creatine kinase (CK) and lactate dehydrogenase (LDH) are biomarkers of tissue damages including myopathy and myocardial infarction. Here, Patrick Sulem and colleagues perform a genome-wide association study to identify common and rare genetic variants that associates with serum CK or LDH levels.